Bias-free true random number generation using superconducting nanowire single-photon detectors. (13th June 2016) - He, Yuhao; Zhang, Weijun; Zhou, Hui; You, Lixing; Lv, Chaolin; Zhang, Lu; Liu, Xiaoyu; Wu, Junjie; Chen, Sijing; Ren, Min; Wang, Zhen; Xie, Xiaoming
Abstract: We demonstrate a bias-free true random number generator (TRNG) based on single photon detection using superconducting nanowire single photon detectors (SNSPDs). By comparing the photon detection signals of two consecutive laser pulses and extracting the random bits by the von Neumann correction method, we achieved a random number generation efficiency of 25% (a generation rate of 3.75 Mbit s −1 at a system clock rate of 15 MHz). Using a multi-channel superconducting nanowire single photon detector system with controllable pulse signal amplitudes, we detected the single photons with photon number resolution and positional sensitivity, which could further increase the random number generation efficiency. In a three-channel SNSPD system, the random number bit generation efficiency was improved to 75%, corresponding to a generation rate of 7.5 Mbit s −1 with a 10 MHz system clock rate. All of the generated random numbers successfully passed the statistical test suite.